2016
DOI: 10.18512/1980-6477/rbms.v15n3p398-409
|View full text |Cite
|
Sign up to set email alerts
|

HÍBRIDOS DE MILHO INOCULADOS COM Azospirillum brasilense SOB DIFERENTES DOSES DE NITROGÊNIO

Abstract: RESUMO -Microrganismos do gêneroAzospirillum possuem o potencial de melhorar o desenvolvimento e a produção da cultura do milho. Porém as respostas dos híbridos de milho não são iguais frente à inoculação com estes microrganismos, devido a possível especificidade na interação entre genótipo e microrganismo e os diferentes manejos adotados. Desta forma, objetivou-se com este trabalho avaliar o desenvolvimento e a produtividade de dez híbridos a fim de indicar entre esses híbridos os mais responsivos quando subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
1
Order By: Relevance
“…Of the genotypes used, 67% performed better using chemical fertilization when evaluating PROL and 78% of the genotypes had better responses regarding NGR in the treatment with nitrogen. Cadore et al (2016) observed that inoculation did not increase the variables analyzed, such as ear length, grains per row, and grain yield while studying the effect of inoculation with Azospirillum brasilense on hybrid maize under different nitrogen doses. According to Leben et al (1987), the inconsistency of positive results is frequent with rhizobacteria that promote plant growth, especially in field conditions.…”
Section: Resultsmentioning
confidence: 94%
“…Of the genotypes used, 67% performed better using chemical fertilization when evaluating PROL and 78% of the genotypes had better responses regarding NGR in the treatment with nitrogen. Cadore et al (2016) observed that inoculation did not increase the variables analyzed, such as ear length, grains per row, and grain yield while studying the effect of inoculation with Azospirillum brasilense on hybrid maize under different nitrogen doses. According to Leben et al (1987), the inconsistency of positive results is frequent with rhizobacteria that promote plant growth, especially in field conditions.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, using this bacterium makes nitrogen available through biological fixation (Pedrinho et al 2010;Dartora et al 2013) and biocontrol of plant pathogens. These factors directly enhance root growth, thus increasing crop productivity (Milléo and Cristófoli 2016;Cadore et al 2016). A study by Dartora et al (2016) and Di Salvo et al (2018) found that combining nitrogen fertilizer and seed inoculation with microorganisms increased maize growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…O fornecimento inadequado de nitrogênio (N) na cultura do milho (Zea mays) é um dos principais fatores restritivos ao rendimento de grãos, pois, é uma das culturas mais exigentes em fertilizantes, sobretudo os nitrogenados, que desempenham papel fundamental nos processos bioquímicos da planta (Sichocki et al, 2014;Oliveira et al, 2018). Logo, a obtenção do máximo potencial produtivo do milho está condicionada ao fornecimento apropriado de N (Santos et al, 2013), Devido ao elevado custo econômico e ambiental do processo industrial de fabricação de fertilizantes minerais, aliado ao aumento da demanda por alimentos, tornase importante a busca por práticas agrícolas que visem racionalizar o uso de N pelas plantas (Cadore et al, 2017). Diante desse cenário, uma estratégia bastante interessante e vantajosa é o uso de insumos biológicos na agricultura.…”
Section: Introductionunclassified